Analisis Kerusakan Material Screen Wall Tube Superheater PLTU Uboh Banten 3 Lontar Unit 1 - Sahlan Sahlan; Nurmiati Pasra; M. Rizki Fariz (Sekolah Tinggi Teknik - PLN, 2015)
Material Screen Wall tube superheater PLTU UBOH Banten 3 Papyrus that has received the damage unit 1 material form fatigue that happened in permukaanya so that these plants need to be fired withdrawn for some time. Considering the importance of the role a power plant in the context of fulfilling present, management needs national, of course dismissal plant operations should be avoided because such as this can lead to a loss for both sides producers and consumers. The importance screen wall tube superheater which functions as a partition or curtain from superheater tube, in writing bachelor theses will test material screen wall tube superheater with various testing method of analysis of other chemical composition (spark oes), analysis of violent methods vickers),SHEM and EDS and analysis metalografi where it is hoped that it can be expressed the analysis of the process was badly and the reasons why components that can be destroyed and damaged.